2020
DOI: 10.1002/aocs.12365
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Model for Assessment of the Risk of Mold Growth in Rapeseeds Stored in a bulk as a Decision Support Tool for Postharvest Management Systems

Abstract: Reliable prediction of the risk of mold development in a stored bulk of rapeseeds may help to maintain seed quality and ensure the highest quality and safety of cooking oil. Mathematical models based on predictive microbiology that are able to assess the risk of fungal growth and the mycotoxins formation in a stored seed ecosystems are promising prognostic tools, which may improve postharvest management systems. The aim of the study was to develop a predictive model of fungal growth in bulks of rapeseeds store… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Given that numerous primary models have not been validated for accuracy [53,54], some models could not accurately predict mold growth in indoor environments [52,55]. The goodness of fit of modeling was determined using the coefficient of determination (Adj.R 2 ) [49,56], root mean square error (RMSE) [31,57], accuracy factor (A f ) and deviation factor (B f ) [31,38,52]. The RMSE indicates the average error, while Adj.R 2 represents the proportion of the variance.…”
Section: Model Accuracy Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that numerous primary models have not been validated for accuracy [53,54], some models could not accurately predict mold growth in indoor environments [52,55]. The goodness of fit of modeling was determined using the coefficient of determination (Adj.R 2 ) [49,56], root mean square error (RMSE) [31,57], accuracy factor (A f ) and deviation factor (B f ) [31,38,52]. The RMSE indicates the average error, while Adj.R 2 represents the proportion of the variance.…”
Section: Model Accuracy Evaluationmentioning
confidence: 99%
“…For accuracy of the two primary models, the A f and B f of both models were within the acceptable range [68] but the Gompertz model values were closer, which means that the Gompertz model has a higher accuracy and smaller deviation. Jolanta Wawrzyniak et al [31] evaluated the risk of mold and its toxins in stored seeds based on a mathematical model of predictive microbiology, and found that the prediction model established based on the modified Gompertz model had a good predictive ability (Adj.R 2 = 0.90, RMSE = 0.547). In this study, the Adj.R 2 under different conditions was above 0.90 (Tables 1 and 2), but the RMSE was high, which means these two primary models might cause large errors.…”
Section: Accuracy Of the Predictive Model And Parameter Determinationmentioning
confidence: 99%
See 1 more Smart Citation